Confining sulfur in double-shelled hollow carbon spheres for lithium-sulfur batteries - Yuan, Changzhou (2013)
Going into their shell: A novel carbon–sulfur nanocomposite has been synthesized by confining sulfur in double-shelled “soft” carbon hollow spheres (see figure) with high surface area and porosity. This carbon–sulfur nanocomposite shows outstanding electrochemical performance when evaluated as a cathode material for lithium–sulfur batteries.